Pervaporation performance of composite poly(dimethyl siloxane) membrane for organic acids removal - Nur Amalina Muhamad Zaidi (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Pervaporation and vapour permeation are membrane-based process for separating binary or multi-component mixtures of miscellaneous organic fluids. This membrance-based separation process can pontentially be used for recovery of organic acids from waste stream. This method is effective since it is less energy consuming, low cost and high pontential to recover organic acid from water mixture. Pervaporation utilizing poly (dimethly siloxane) membrane (PDMS) for acetic acid removal. PDMS membrane is categorized as a dense and hydrophobic membrane, which restricts the water molecule and allows the permeation of other organic materials to pass through the membrane matrix. In this study, PDMS membrane was laboratory syntheisize. The preparation of the membrane was done by phase inversion-immersion precipitation method. N-methyl-2-pyrrolidone (NMP) was used as a solvent to disolve the polyphenylsulfone (PPSU) resins. The composition of solutuion is prepared in five different polymer concentrations which are (25-30)%. Membrane morphology and structure is analyzed by Field Emission Electron Microscope (FESEM) analysis and Fourier Transform Infrared Spectroscopy (FTIR) analysis.